WHAT CAN WE LEARN FROM THE IMITATION OF CHRIST OF THOMAS A KEMPIS? - Tirza Rachmadi (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2019)
This article seeks to promote an interest of the audience to read the Imitation of Christ, the second most read book by both Protestants and Roman Catholics after the Bible. The book is dated to pre-Reformation time and provides fruitful soil for the Reformation by keeping close to the Scripture and the primacy of Christ. The book’s three main motives sound strangely familiar to modern ears: the basic pairs of opposition coloring the current fabric of reality, the sovereignty of God, and the obedience of God’s people. Even today the book remains fresh with its honesty and practical value, despite its being firmly grounded in doctrinal rocks. KEYWORDS: Imitation of Christ; Thomas a Kempis; practical theology